2020
DOI: 10.7589/jwd-d-20-00036
|View full text |Cite
|
Sign up to set email alerts
|

Body Weight as an Indicator of Vulnerability to Domestic Cat Predation for Juveniles of Three Species of Cottontail Rabbits (Sylvilagus spp.) in Colorado, USA: Implications for Release Criteria

Abstract: Cottontail rabbits ( Sylvilagus spp.) are frequently admitted to wildlife rehabilitation facilities due to predation by domestic cats ( Felis catus). Our retrospective study (2015–19) of three species ( Sylvilagus audubonii, Sylvilagus floridanus, and Sylvilagus nuttallii) indicated that once juveniles reached a weight over 220 g, they were unlikely to present due to domestic cat interactions. This information should be incorporated into release criteria for these species.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(14 citation statements)
references
References 3 publications
0
14
0
Order By: Relevance
“…We did not have enough data to conduct occupancy analyses on the non‐targeted mammal species. Although beyond the focus of this study, future research could evaluate interactions among coyote, cats, and cottontails, as other studies have found that cat abundance is higher in residential yards that do not have coyotes, and domestic cats can prey on lagomorph species (Kays et al, 2015; McGregor et al, 2020; Paul & Friend, 2020). Additionally, other research has found that mesopredators do not change temporal or spatial activity in response to predators like coyotes when humans are present, indicating that humans play a “predator”‐like role in urban systems similar to our study area (Moura et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…We did not have enough data to conduct occupancy analyses on the non‐targeted mammal species. Although beyond the focus of this study, future research could evaluate interactions among coyote, cats, and cottontails, as other studies have found that cat abundance is higher in residential yards that do not have coyotes, and domestic cats can prey on lagomorph species (Kays et al, 2015; McGregor et al, 2020; Paul & Friend, 2020). Additionally, other research has found that mesopredators do not change temporal or spatial activity in response to predators like coyotes when humans are present, indicating that humans play a “predator”‐like role in urban systems similar to our study area (Moura et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, this provides the rationale to include admission as a category. Because the state of eastern cottontails on admission depicts the type of care they will begin to receive (Burton & Doblar 2004;Garrigan et al 2016;Loyd et al 2017;McRuer et al 2017;Long et al 2020;Paul & Friend 2020;Timm & Kime 2020;Hanson et al 2021), we can expect admission information to be included in detail in the literature.…”
Section: Rationalementioning
confidence: 99%
“…A conditioning period or outdoor housing may help an eastern cottontail become familiarized with their surroundings and forage in a safer environment prior to being released (Cherney & Nieves 1991;Diehl & Stokhaug 2012;Ford & Dubé 2019), but it is unknown whether this period is beneficial to released eastern cottontails in the long term. Housing infant eastern cottontails indoors in quiet areas only could be a way to minimize stress while in care (Reese 1992a;Jijón et al 2007;Oberly 2015;Paul & Friend 2017;Santos 2018;Tseng 2019). As housing can have a significant effect on an eastern cottontail's welfare and potentially their outcome, it is important to be included in this analysis.…”
Section: Rationalementioning
confidence: 99%
“…At each spatial scale, observation data from all cameras located within each grid cell were pooled to create daily detection histories (detected = 1, not detected = 0, not surveyed = NA) for the respective cell using the package "CamtrapR" in R version 4.1.2 (Niedballa et al, 2016;RStudio Team, 2019;R Core Team, 2020). Species included in this analysis were domestic cat due to its centrality to the research questions, and eastern chipmunk (Tamias striatus), eastern cottontail (Sylvilagus floridanus), eastern gray squirrel (Sciurus carolinensis), groundhog (Marmota monax), and white-footed mouse (Peromyscus leucopus) because they are native species known to be depredated by domestic cats (George, 1974;Loyd et al, 2013;Paul and Friend, 2020;Herrera et al, 2022). Raccoon (Procyon lotor), red fox (Vulpes vulpes), and Virginia opossum (Didelphis virginiana) were also included because they are disease vectors or are otherwise known to be a risk to cats through direct conflict or interference competition (Carey and McLean, 1983;Jenkins et al, 1988;Sogliani and Mori, 2019;Zecca et al, 2020;Hennessy and Hild, 2021).…”
Section: Observation Datamentioning
confidence: 99%